Perbedaan Pengaruh Antara Mobilisasi Saraf Dan Myofacial Release Terhadap Penurunan Nyeri Pada Pasien Carpal Tunnel Syndrome - Budi Utomo; Yulianto Wahyono (Poltekkes Kemenkes Surakarta, 2017)
Abstract : Nerve Mobilization, Myofacial Release, Carpal Tunnel Syndrome. Carpal tunnel syndrome (CTS) is defined with signs and symptoms resulting from compression of the median nerve at the wrist. CTS lead to discomfort and pain, limited daily activities, sleep deprivation and the inability to work. Nerve mobilization is manipulative technique in which the nerve tissue is moved and stretched out both motions relative to the surrounding (interface mechanical) or with the development of tension. Myofascial Release (MFR) refers to massage techniques, instructions for stretching the fascia and releasing bonds between fascia and integument, muscles, bone, with the aim to relieve pain, increase range of motion and balance the body. Some research concluded the difference in the length of time the treatment is with a shorter time can produce significant pain reduction. The aim of this study was to determine the effect of the difference between the provision of nerve mobilization and myofacial release to the reduction of pain in patients with carpal tunnel syndrome. This research is a quasi experimental study with two group pre test and post test control design. The subjects were all patients diagnosed with carpal tunnel syndrome who came to the clinic physiotherapy Dr. Moewardi Surakarta hospital who met the inclusion criteria, exclusion and drop out. Number of research subjects in group I, amounting to 8 people and group II amounted to 7 people. Group I was treated nerve mobilization and group II were treated Myofacial release. Treatment was given 2 times per week for 3 weeks. Results: (1) mobilization of the nerve may reduce pain in patients with CTS (p = 0.012), (2) MFR can reduce a patient's pain CTS (p = 0.018), (3) there is no difference between mobilization nerves and MFR to reduce pain CTS patients (p= 0.189).